A survey of southern hemisphere meteor showers. (May 2018) - Jenniskens, Peter; Baggaley, Jack; Crumpton, Ian; Aldous, Peter; Pokorny, Petr; Janches, Diego; Gural, Peter S.; Samuels, Dave; Albers, Jim; Howell, Andreas; Johannink, Carl; Breukers, Martin; et al.
Abstract: Results are presented from a video-based meteoroid orbit survey conducted in New Zealand between Sept. 2014 and Dec. 2016, which netted 24, 906 orbits from +5 to −5 magnitude meteors. 44 new southern hemisphere meteor showers are identified after combining this data with that of other video-based networks. Results are compared to showers reported from recent radar-based surveys. We find that video cameras and radar often see different showers and sometimes measure different semi-major axis distributions for the same meteoroid stream. For identifying showers in sparse daily orbit data, a shower look-up table of radiant position and speed as a function of time was created. This can replace the commonly used method of identifying showers from a set of mean orbital elements by using a discriminant criterion, which does not fully describe the distribution of meteor shower radiants over time.